Investment Pattern, Preferences and Financial Mangement Practices of Wesleyan University-Philippines Employees - Castillo, Manuel P.; Mamaclay, Ali G.; Rivera, Kevin M. (Advances in Social Sciences Research Journal, 2021)
This study determined the investment pattern, preferences, and practices of Wesleyan University-Philippines employees with the used of descriptive correlational methods of research, and the data were collected using a researcher-made survey questionnaire. Respondents of the study were the 305 employees chosen purposively. The result shows that most of the respondents belonged within the age range of 19 – 28 years old, married, a college graduate with 1 – 6 years in service, permanent, had a monthly income of 10000-21000 and had other sources of income from their husband/wife income. Likewise, most of the respondents had a saving for an emergency and unforeseen circumstances, had an investment and invested 1 – 5 percent of their income. Most of them had a saving account, intended to invest the money to more than five years in which the principal amount is secured, invested in the private sector, and expected to grow steadily. Similarly, this study found out that the respondents sometimes practice the five indicators of financial management practices used in the study. Moreover, profile variables were significantly correlated with financial management practices. Age, number of years in service, employment status, monthly income, and other sources of income were significantly associated with money management practices. Similarly, a number of years in service were correlated considerably with savings management practices. Finally, age, employment status, and other sources of income were significantly associated with investment management practices. Further, there is a significant difference in the respondents’ assessment in all indicator of financial management practices.